2013
DOI: 10.1371/journal.pone.0064278
|View full text |Cite
|
Sign up to set email alerts
|

Differential Cytotoxic Activity of a Novel Palladium-Based Compound on Prostate Cell Lines, Primary Prostate Epithelial Cells and Prostate Stem Cells

Abstract: The outcome for patients with advanced metastatic and recurrent prostate cancer is still poor. Therefore, new chemotherapeutics are required, especially for killing cancer stem cells that are thought to be responsible for disease recurrence. In this study, we screened the effect of a novel palladium-based anticancer agent (Pd complex) against six different prostate cancer cell lines, and primary cultures from seven Gleason 6/7 prostate cancer, three Gleason 8/9 prostate cancer and four benign prostate hyperpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…After counting the apoptotic cells, nearly 38% of apoptosis was evident after 72 h of treatment of DU145 cells with 27 μM of prepared palladium complex. According to similar work carried out by Ulukaya et al, 18 palladium complex has demonstrated extensive growthinhibitory effect against prostate cancer cells. They claimed that the Pd complex induced DNA damage and also cell death in prostate cancer cells.…”
Section: Tunel Assaymentioning
confidence: 84%
“…After counting the apoptotic cells, nearly 38% of apoptosis was evident after 72 h of treatment of DU145 cells with 27 μM of prepared palladium complex. According to similar work carried out by Ulukaya et al, 18 palladium complex has demonstrated extensive growthinhibitory effect against prostate cancer cells. They claimed that the Pd complex induced DNA damage and also cell death in prostate cancer cells.…”
Section: Tunel Assaymentioning
confidence: 84%
“…In addition, using a panel of cell lines may also not be a great improvement because results from experiments in cell lines have been seen here and in other studies to be quite different from primary cells [26][27][28] . Cells in primary cultures have compensatory signaling pathways that have been lost in cell lines, and so an inhibitor that works well in cell lines may be less effective or ineffective in primary cultures [28] .…”
Section: Discussionmentioning
confidence: 92%
“…Several recent studies using primary prostate epithelial cultures have shown the heterogeneity of response to current and novel treatments including autophagy [20,26] , necrosis [27] , cell differentiation [44,45] , apoptosis, DNA damage [15,27] , cell cycle arrest and senescence [20] [ Figure 6]. Several of these can act as a crossroads for a cell resulting in cell survival or cell death and if we are able to predict which response may occur then we may be able to manipulate it towards cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Are they selected because the results are consistent with the original hypothesis, or should they cover the same or different prostate cancer phenotypes? One sample each from castration resistant and hormone sensitive cells is by no means statistically significant, however the analysis of 10-12 tumors of a similar Gleason grade in patients with a similar hormone naïve background should provide statistically relevant results, which also can reflect, in their diversity, the patient specific variation we see in responses to many drugs [23] . Although clonal selection can also be an argument against primary cultures, they at least do have a heterogeneous phenotype (several cell subpopulations are represented), they can be differentiated in 2D culture to give rise to other, more luminal, cell populations and when routinely used at low passages the amount of time-dependent selection pressure is reduced.…”
Section: Overcoming Clonal Biasmentioning
confidence: 99%